ANALISIS KEMAMPUAN PEMAHAMAN MATEMATIS DAN TINGKAT KEPERCAYAAN DIRI PADA SISWA MTs - Nuraeni - Nuraeni; Evon Siti Mulyati; Rippi Maya (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
This research is aimed to analyze the mathematical understanding ability and self confidence of MTs students. It is also to analyze the correlation between those two variables. This study used a correelation method with quantitative approach. The reaserch subject are students of MTs in Bandung Barat. With the sample are 18 students of VIII grade. Instruments used in this resarch are mathematical understanding ability test, as many as 5 essay question in each question load one indicator of mathematical understanding ability. There are 20 scale statments taht 4 indicator. The result of this research can be concluded the mathematical comprehension ability and level of selfcompidence students is stin low there is correlation that influence each other between mathematical understanding ability and self confidence of students